Sistem Informasi Manajemen Rancangan Anggaran Dan Pendapatan Sekolah Pada Dinas Pendidikan Kota Magelang - Krisna Widatama; Beni Suranto (INTEK : Jurnal Informatika dan Teknologi Informasi, 2018)
The Budget Information and School Revenue Management Information System at the Magelang City Education Office is an application used by the treasurer to draft up to the stages of prepar-ing the budget report and income of Elementary Schools in the City of Magelang. This applica-tion can do the process of calculating the budget, revenue budget, and display the percentage of expenditure based on a particular account code. The output of this system is direct shopping re-ports, indirect expenditure, monthly expenditure, income, a list of school account codes, a list of programs, school activities, and A2 receipts that are used as proof of monthly expenditure. The output of the system can make it easier for the treasurer in designing the school budget, because the results of calculations produced by the system are accurate and the system can also make reports automatically when the treasurer has designed the budget and school income.